2022
DOI: 10.1101/2022.08.30.22279401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalizable electroencephalographic classification of Parkinson’s Disease using deep learning

Abstract: There is growing interest in using electroencephalography (EEG) and deep learning (DL) to aid in the diagnosis of neurological conditions like Parkinson's Disease (PD). Many existing DL approaches to classify PD from EEG data cite performance metrics in the high 90% accuracies, but may be grossly overestimating their real-word capabilities due to information-leakage between training and testing data. Our aim was to characterize the potential of deep learning for classifying PD using a conservative training app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Firstly, we achieved an increase of approximately 10% in accuracy compared to previous methods. Some researchers have reported moderate accuracy results such as 88.51% by Shah [39], 69.2% by Sugden [43], 85.4% by Anjum et al [15], 78% by Chaturverdi et al [42], and 88.5% by Aljalal et al [48]. Other researchers reported quite high accuracy results, such as 99.2% by Lee et al [50], 94.1% by Sugden [43], 99.58% and 99.41% by Aljalal [48,51], 94.3% by Vannesta [45], and 99.62% by Yuvaraj [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we achieved an increase of approximately 10% in accuracy compared to previous methods. Some researchers have reported moderate accuracy results such as 88.51% by Shah [39], 69.2% by Sugden [43], 85.4% by Anjum et al [15], 78% by Chaturverdi et al [42], and 88.5% by Aljalal et al [48]. Other researchers reported quite high accuracy results, such as 99.2% by Lee et al [50], 94.1% by Sugden [43], 99.58% and 99.41% by Aljalal [48,51], 94.3% by Vannesta [45], and 99.62% by Yuvaraj [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported moderate accuracy results such as 88.51% by Shah [39], 69.2% by Sugden [43], 85.4% by Anjum et al [15], 78% by Chaturverdi et al [42], and 88.5% by Aljalal et al [48]. Other researchers reported quite high accuracy results, such as 99.2% by Lee et al [50], 94.1% by Sugden [43], 99.58% and 99.41% by Aljalal [48,51], 94.3% by Vannesta [45], and 99.62% by Yuvaraj [46]. However, some studies in the literature reported have had issues, such as data leakage from the training dataset to the test dataset, unbalanced classes, demographically unmatched groups, or artificially replicated EEG records, leading to very high accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Their model accomplished 69.2%, 66.5%, and 72.2% of accuracy, sensitivity, and specificity, respectively, epoch-wise performance. Whereas 77.2%, 83.5%, and 71.0% of accuracy, sensitivity, and specificity subject-wise performance [31]. In another attempt, Shaban et al proposed a 20 layered CNN architecture for classifying the PD-on medication from PD-Off medication and the healthy controls.…”
Section: Literature Reviewmentioning
confidence: 99%